Ballistic performance of multi-layered B4C ceramic and UHMWPE fibre laminate targets subjected to hypervelocity impact by tungsten alloy ball. (November 2022) - yongjun, Deng; yi, Wang; kefo, Qu; yong, Yao
Abstract: This paper carry out the experiments to test the anti-penetration performance of ceramic/fiber composite targets of three composite configurations against high-speed penetration of tungsten alloy spherical projectiles. Then the author adopts the combined FEM-SPH method to establish the corresponding numerical simulation model and carries out the parameter analysis of the optimal working conditions of ceramic/fiber composite targets through numerical simulation. The results of the study are as follows: (1) the ceramic plate is placed at the first layer as the bullet-resisting layer, which is designed to shatter the projectile, effectively improving the anti-penetration performance of the ceramic and fiber composite target, but the broken fragments of ceramic target plate may bring secondary damage.(2) the aluminum alloy plate is at the surface layer, which prevents the splash of the broken pieces but reduces the anti-penetration performance of the original ceramic/fiber composite target. The aluminum alloy of certain thickness is at interlayer, which delivers a better anti-penetration performance than making aluminum alloy plate at the surface layer. However, the anti-penetration performance of that is worse than the ceramic/fiber composite target of the same surface density.